2017
DOI: 10.1017/rdc.2017.137
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Flow Nanofiltration of Contaminated Protein-Containing Material: State of the Art

Abstract: Radiocarbon (14C) dating of protein-containing material (collagen, hair/wool, silk, leather) contaminated with extraneous carbon (e.g. humic substances) might result in unreliable dates when pretreated with the conventional but inadequate protocols. In this study cross-flow nanofiltration was applied to pretreated, protein-containing material. This method is able to remove low-molecular and high-molecular weight contaminants as demonstrated in previous studies. The sample quality improvement by cross-flow nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Nevertheless, to diminish or eliminate this problem, washing the ultrafilters with weak acid (0.01 N HCl) can increase the yield of collagen, hence decreasing the contaminant-to-protein ratio [ 78 ]. It has also been suggested that ultrafiltration of the gelatin will fail to remove high-molecular-weight contaminants, which could be eliminated by means of ceramic nanofiltration (tests applied to nanopores of 368 and 450 Da) of gelatin previously hydrolysed to amino acids [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to diminish or eliminate this problem, washing the ultrafilters with weak acid (0.01 N HCl) can increase the yield of collagen, hence decreasing the contaminant-to-protein ratio [ 78 ]. It has also been suggested that ultrafiltration of the gelatin will fail to remove high-molecular-weight contaminants, which could be eliminated by means of ceramic nanofiltration (tests applied to nanopores of 368 and 450 Da) of gelatin previously hydrolysed to amino acids [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The C:N ratio, the collagen yield and the carbon and nitrogen contents are checked, as well as the color and texture of the extracted collagen, to control the collagen quality (Van Klinken 1999). Commonly, well-preserved collagen is white and fluffy while degraded collagen appears brown in color and crystalline (Boudin et al 2017). For modern bones, the percentage of collagen is around 20 %wt and after burial, the collagen content drops.…”
Section: Collagen Extractionmentioning
confidence: 99%
“…At RICH, bones containing less than 2% collagen are considered as poorly preserved. Nevertheless, we date all collagen samples having a C:N ratio between 2.9 and 3.6 as C:N is used to indicate contamination (Boudin et al 2017). The degree of preservation is also followed by the carbon and nitrogen contents.…”
Section: Collagen Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burleigh and Baynes-Cope (1983) mentioned the difficulties in successfully treating silk samples prior to 14 C measurements. Recently, Boudin et al (2011Boudin et al ( , 2014Boudin et al ( , 2016Boudin et al ( , 2017 systematically investigated a preparation procedure for archeological wool and silk materials to eliminate contaminating materials for high-accuracy 14 C dating. Kim et al (2008) also studied preparation procedures of silk samples, and used silk textiles separated from modern neckties thought to be produced in the 1970s and measured 14 C contents of untreated silk samples including dyes and three silk protein fractions of different molecular weight ranges that were separated from decomposed silk fibroin using ultrafiltration concentrators.…”
Section: Introductionmentioning
confidence: 99%